Information design in multi-stage games - Miltiadis Makris; Ludovic Renou (Queen Mary University of London, School of Economics and Finance, 2018)
We consider multi-stage games, where at each stage, players receive private signals about past and current states, past actions and past signals, and choose actions. We fully characterize the distributions over actions, states, and signals that obtain in any (sequential) communication equilibrium of any expansion of multi-stage games, i.e., when players can receive additional signals about past and current states, past actions, and past and current signals (including the additional past signals). We interpret our results as revelation principles for information design problems. We apply our characterization to bilateral bargaining problems.
Keywords: C73; D82; 330; multi-stage games; information design; communication equilibrium; sequential communication equilibrium; information structures; Bayes correlated equilibrium; revelation principle